Anticipation of Monopoly Practices for Umkm in the Indonesian Capital Partner Area - Setiyo Utomo; Deny Slamet Pribadi (Universitas Islam Lamongan, 2025)
The purpose of this study is to find out the legal protection of Small and Medium Enterprises (SMEs) against monopolistic practices at the nation's capital/IKN and find out the role of the government to eradicate the monopolistic practices against Small and Medium Enterprises (SMEs) at the nation's capital/IKN in the business competition. The conclusion showed 1) the legal protection against UMKM consist of preventive legal protection and repressive legal protection at the nation's capital/IKN. Preventive protection such as prevention, the Big Businessman has forbidden to make agreements and other acts which tend to make damages to other businessman competitor and if the agreement makes unfair business competition for UMKM. However the repressive protection such as giving sanctions like administrative sanction, criminal punishment principal, and another criminal punishment. 2) the role of the government to eradicate the monopoly practice business at the nation's capital/IKN has been regulated in several regulations. This government role such as providing the financial facility, infrastructure, the information facilities services, the partnerships and easy business licensing, providing facilities and incentives, and managing the partnerships and structuring modern market locations.